COMPARATIVE EFFECTS OF SOME MEDICINAL PLANTS ON SODIUM ARSENITE-INDUCED CLASTOGENICITY - ADEWALE ADETUTU; OLUSOJI ABIODUN OWOADE; OLUBUNMI SIMEON OYEKUNLE (International Journal of Pharma and Bio Sciences, 2013)
The effectiveness of crude methanolic extracts of Bridelia ferruguinea, Tridax procumbens, Ocimum gratissimum and Lawsonia inermis against clastogenicity induced by sodium arsenite (SA) was evaluated using an in-vivo rat bone marrow cell micronuclei test and the DPPH radical scavenging assay. Methods: 50 mg/kg body weight of the extracts were given by gavaging to the rats in five groups for seven consecutive days as a dietary supplement followed by a single dose of SA (2.5 mg/kg per body weight) which was administered intraperitoneally. Results: Preliminary screening of the clastogenicity showed that aqueous extracts of these plants have no significant clastogenic activity in rat. Pre-treatment of rats for seven days with extracts orally before exposure to SA resulted in a significant reduction of the degree of formation of micronuclei in polychromatic erythrocytes of the bone marrow. The degree of reduction of arsenite was of the order B. ferrugenia > O. gratissimum>T. procumbens > L. inermis. Phytochemical analysis carried out on the extracts revealed the presence of known chemical constituents. The phytochemical constituents might be responsible for the strong DPPH scavenging activities exhibited by the plant extract. Conclusion: This study suggests that B. ferruguinea, T. procumbens, O. gratissimum, and L. inermis extracts have anticlastogenic potential and possibly due to their antioxidant properties.Therefore, the plant extracts may be useful in the stoppage of arsenite-induced toxicity in areas where arsenic is a potential environmental contaminant.